Ethnobotany of suweg (Amorphophallus paeoniifolius): Folk classification, habitat, and traditional conservation in Cisoka Village, Majalengka District, Cimanuk Watershed Region, Indonesia - ASEP ZAINAL MUTAQIN; DENNY KURNIADIE; JOHAN ISKANDAR; MOHAMAD NURZAMAN; Ruhyat Partasasmita (Society for Indonesian Biodiversity, 2020)
Abstract. Mutaqin AZ, Kurniadie D, Iskandar J, Nurzaman M, Partasasmita R. 2020. Ethnobotany of suweg (Amorphophallus paeoniifolius): Folk classification, habitat, and traditional conservation in Cisoka Village, Majalengka District, Cimanuk Watershed Region, Indonesia. Biodiversitas 21: 546-555. Amorphophallus paeoniifolius (Dennst.) Nicolson or suweg is commonly called in Sunadese of West Java as suweg that is a species of tuber growing in many regions of the world, including in the Cimanuk Watershed, West Java Province, Indonesia. A. paeoniifolius usually grows in rural areas of West Java in some agroecosystem types, including the homegarden, garden, and mixed garden system. This plant species, in contrast to other tuber species, such as taro, has not been intensively cultivated by rural community in West Java. Even though A. paeoniifolius has not been intensively cultivated, this plant species in the future have the potential to be used for various purposes for human being. Because A. paeoniifolius, one of plant tubers, has a high resistance to unpredictable environmental changes, such as climate change, pest disruption, and easy to maintain. This study aimed to elucidate the traditional ecological knowledge (TEK) of rural people of Cisoka Village, Cikijing Sub-district, Majalengka District of Cimanuk Watershed, West Java on folk classification, habitat, and traditional conservation of A. paeoniifolius. The method used in this study was qualitative. Field data collection was undertaken by observation and semi-structured interviews or deep interviews with competent informants. The results of study showed that the rural population of Cisoka Village, Majalengka District, has recognized two kinds of Amorphophallus. Firstly, Amorphophallus is a commonly consumed that is called suweg which has scientific name as Amorphophallus paeoniifolius (Dennst.) Nicolson. Secondly, Amorphophallus is recognized as not commonly consumed which is called 'iles-iles' (Amorphophallus variabilis Blume). Both species can be traditionally classified based on morphology (tubers, leaf blade and petioles, and flowers), habitat, utilization, cultivation, and suitability of growing places. Specifically, A. paeoniifolius, grows in various conditions, growing at non-cultivated lands, such as forests and cultivated land, such as homegarden, garden, mixed-garden, and rice fields, or pond edges, but predominantly grows in homegardens and gardens. Some of these lands are hieum or shaded areas and negrak or open areas. A. paeoniifolius starts to grow and develop at the beginning of the rainy season until approaching the dry season, which is characterized by yellowing and falling of petiole. Conservation of A. paeoniifolius has been based on tradition is carried out by the rural community through storage/ preparation of seeds, which does not destroy A. paeoniifolius that grows in several types of agroecosystems, and is managed semi-intensively in several types of agroecosystems such as homegardens and gardens.